The Mediating Role of Coping Style: Associations Between Intimate Partner Violence and Suicide Risks Among Chinese Wives of Men Who Have Sex With Men - Wu, Weizi (Journal of interpersonal violence, 2021)
The wives of men who have sex with men, known as “Tongqi” in China, have increasingly attracted public attention due to their potential risks of suicide and sexually transmitted infections and HIV. However, few studies have explored the association between intimate partner violence (IPV) and suicide risk or the mediating effect of coping style on these associations among Tongqi in China. To describe these relationships, a cross-sectional online survey was conducted in China from February 2016 to February 2017. A questionnaire, which consisted of the Revised Conflict Tactics Scales, the Simplified Coping Style Questionnaire, the Beck Scale for Suicidal Ideation, and reports of suicide attempts, was completed by 178 Chinese Tongqi. Bootstrap tests were performed to determine the mediating role of coping styles on the association between IPV and suicide risks. The median IPV score was 14 (range: 0-50), with the domain of negotiation ranking highest. The average coping style score was .37±.73; 61.2% of Tongqi have had suicidal ideation, and 11.8% had attempted suicide. IPV was significantly correlated with suicidal ideation (rs = .19, p < .01) and suicide attempts (rs = .29, p < .001). Participants with a negative coping style had higher suicidal ideation (rs = –.39, p < .01) and suicide attempts (rs = –.22, p < .01). Coping style had a full mediating effect on the association between IPV and suicidal ideation and a partial mediating effect on suicide attempts. Chinese Tongqi experienced high level of IPV and suicide risks. IPV contributed to the suicide risks of Chinese Tongqi, but these associations were mediated by coping style. Therefore, interventions to improve mental health and prevent suicide risks of Chinese Tongqi should focus on helping them develop a positive coping style to achieve the goal of Healthy China in 2030.